Antero-medial Transposition of Inferior Oblique for a Superior Oblique Palsy: A Case Report: Doi: 10.36351/pjo.v39i2.1526 - Syeed Mehbub Ul Kadir; Mamunur Rashid Chowdhury (Pakistan Journal of Ophthalmology, 2023)
A 29-year-old female presented with large-angle hypertropia, and small-angle exotropia associated with inferior oblique over action (IOOA). Orthoptic examination revealed right hypertropia of 35 PD with 12 PD of exotropia by prism cover test. There was no restriction of ocular motility, but we found right inferior oblique over action. She had a head tilt of approximately 30 degrees towards the left side. The Patient underwent "Antero-medial transposition of the inferior oblique" to correct strabismus. After surgery, she was orthotropic in the primary position with an average head-chin posture. Single approach surgery like the antero-medial transposition with an overacting inferior oblique may help to correct the large angle hypertropia associated with superior oblique (SO) palsy.